Marital Status and Prognostic Nomogram for Bladder Cancer With Distant Metastasis: A SEER-Based Study - Tao, Liangjun; Pan, Xinyuan; Zhang, Lixiang; Wang, Jiawei; Zhang, Zican; Zhang, Li; Liang, Chaozhao (Frontiers in Oncology, 2020)
Background: To investigate the impact of marital status on overall survival (OS) and create a prognostic nomogram predicting OS in distant-metastatic bladder cancer (DMBC) patients. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was explored to recruit DMBC patients from 2010 to 2015. Kaplan–Meier survival analysis was used to compare survival differences among different marital status. Univariate and multivariate analyses were used to screen for prognostic factors and then constructed the nomogram based on Cox proportional hazard regression models. Calibration plot diagrams and concordance index (C-index) were used to verify the prognostic nomogram. Results: Kaplan–Meier curves suggested the significant differences of OS among different marital status existed in total (P<0.001), female (P=0.011) and male (P=0.001) DMBC patients, respectively. Multivariate analysis indicated marital status was an independent prognostic factor for OS of DMBC patients. Nomogram showed the contribution of marital status to predicting OS was small. Other independent prognostic factors included age, grade, histology type, surgery of primary site, chemotherapy and metastasis pattern. By combining seven factors, we constructed a prognostic nomogram for DMBC patients. The C-index of this nomogram for OS prediction was 0.722 (95% CI 0.712-0.732). The calibration curves showed perfect consistency between observed and predictive survival. Conclusions: Marital status was an independent prognostic factor for OS of DMBC patients, but its contribution to predicting OS was small. The prognostic nomogram will provide an individualized evaluation of OS and guidance for suitable treatments in DMBC patients.